A Hearing Screening Protocol for Stroke Patients: An Exploratory Study - Koohi, Nehzat; Vickers, Deborah A.; Utoomprurkporn, Nattawan; Werring, David J.; Bamiou, Doris-Eva (Frontiers in Neurology, 2019)
Background: Auditory impairment post stroke is common and may be due to both peripheral hearing loss and or central auditory processing disorder. When auditory impairment remains untreated, it may impact on patient communication and rehabilitation after stroke. Offering a comprehensive audiological assessment to all stroke patients would be both costly and time-consuming. A brief hearing screening is thus required. Objective: The aim of this study was to determine whether a two-tiered hearing screening approach, with use of a handheld hearing screener and two validated hearing questionnaires could be used as a hearing screening for peripheral hearing loss and central auditory processing disorder in stroke survivors. The sensitivity and specificity of the screening method was analysed. Methods: This was a prospective study conducted in a tertiary neurology hospital. Forty-two consecutive stroke patients were recruited and tested within three to twelve months post-onset of their stroke. Three screening tools for the identification of hearing impairment were evaluated in this study: A handheld hearing screener for determination of peripheral audiometric hearing loss and two validated questionnaires (The Amsterdam Inventory Auditory for Disability and the Hearing Handicap Inventory for Elderly questionnaires) for determination of peripheral hearing loss and/or central auditory processing disorder. Results: The hearing screener had a sensitivity of 92. 59% detecting a hearing loss and specificity of 100%. The greatest test accuracy in identifying a central auditory processing type hearing impairment in stroke patients was found when the handheld hearing screener and the Amsterdam Inventory Auditory for Disability questionnaire were combined. Conclusion: This study is a first step towards addressing the complex auditory needs of stroke survivors in a systematic manner, with the ultimate aim to support their communication needs and long-term recovery and wellbeing. Registration: Project Identification number 11/0469 and REC ref 11/LO/1675